In the rear view mirror - "Mathew, C. K (Comp); Vadanan, Akash S.; Dutta, Udita; Pillai" (Bangalore, 2017)
In this volume called "In the Rear-View Mirror: Reflections of Chief Secretaries," Public Affairs Centre has captured the thoughts and reminiscences of seventeen retired Chief Secretaries of as many states. Each of them have worked in the service of the nation for over three or three-and-a-half decades and possess that rare experience and wisdom few would be able to match. They are witness to the history of India rolling out before their eyes and have participated in the process of nation building in the singular role they have played in top positions in government ending with that of the Chief Secretary.
Keywords: Bureaucrat biography